2007
DOI: 10.1258/026835507780346213
|View full text |Cite
|
Sign up to set email alerts
|

Endovenous laser closure of the perforating vein of the leg

Abstract: There are many options in the treatment of incompetent perforating vein of the leg. An endovenous procedure should be considered as one of the options, especially where tissue around the incompetent perforating vein of the leg is compromised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…15, 16 Kianifard and colleagues 17 performed a randomized clinical trial to investigate the fate of IPVs after saphenofemoral ligation and stripping of the GSV, with or without SEPS, and concluded that IPVs do not remain closed after standard varicose vein surgery and that the addition of SEPS was not associated with significant morbidity but reduced the number of IPVs. [5][6][7]15,16 Recently, Proebstle and colleagues reported laser ablation of 67 IPVs combined with phlebectomy or ablation of the GSV or SSV in 60 patients. [5][6][7]15,16 Recently, Proebstle and colleagues reported laser ablation of 67 IPVs combined with phlebectomy or ablation of the GSV or SSV in 60 patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15, 16 Kianifard and colleagues 17 performed a randomized clinical trial to investigate the fate of IPVs after saphenofemoral ligation and stripping of the GSV, with or without SEPS, and concluded that IPVs do not remain closed after standard varicose vein surgery and that the addition of SEPS was not associated with significant morbidity but reduced the number of IPVs. [5][6][7]15,16 Recently, Proebstle and colleagues reported laser ablation of 67 IPVs combined with phlebectomy or ablation of the GSV or SSV in 60 patients. [5][6][7]15,16 Recently, Proebstle and colleagues reported laser ablation of 67 IPVs combined with phlebectomy or ablation of the GSV or SSV in 60 patients.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Although clinical indications for treatment of incompetent perforator veins (IPVs) have not been defined, many previous reports have suggested that IPVs may contribute to venous hypertension and play an important role in development of chronic venous disease. [5][6][7] It is not uncommon for varicosities to arise from incompetent GSVs without evidence of saphenofemoral reflux; treatment of thigh IPVs with venous reflux into the GSV is usually performed by ablation of non-healthy GSVs, and not by directly managing directly the IPV, 5 but some authors have suggested that treatment of the thigh perforator results in a better outcome, and it has been demonstrated that IPVs play a significant role in recurrence of varicosities after treatment of saphenous veins. (SEPS) and open ligation and division of perforator vein, minimally invasive management of IPVs, known as percutaneous ablation of IPVs, has recently been introduced as a safe and efficacious alternative.…”
mentioning
confidence: 99%
“…8,9 There are also isolated reports of treatment of incompetent perforating veins 10,11 and varicosities themselves. 12 …”
Section: Patient Selectionmentioning
confidence: 99%
“…The alternatives are liquid sclerotherapy 1,5,23 and foam echo‐guided sclerotherapy 24,25 . Some new information concerning the endovascular treatment of PVs and CVs can be found in the literature 26–30 …”
mentioning
confidence: 99%
“…24,25 Some new information concerning the endovascular treatment of PVs and CVs can be found in the literature. [26][27][28][29][30] Our preliminary experience demonstrated that EVLA of PVs and VCs can represent an easier and faster technique and give better results than surgical methods previously proposed.…”
mentioning
confidence: 99%